The Effect of Animation-Guided Mindfulness Meditation on the Promotion of Creativity, Flow and Affect - Chen, Hao; Liu, Chao; Zhou, Fang; Chiang, Chao-Hung; Chen, Yi-Lang; Wu, Kan; Huang, Ding-Hau; Liu, Chia-Yih; Chiou, Wen-Ko (Frontiers in Psychology, 2022)
Creativity is so important for social and technological development that people are eager to find an easy way to enhance it. Previous studies have shown that mindfulness has significant effects on positive affect (PA), working memory capacity, cognitive flexibility and many other aspects, which are the key to promoting creativity. However, there are few studies on the relationship between mindfulness and creativity. The mechanism between mindfulness and creativity is still uncertain. Meditation is an important method of mindfulness training, but for most people who do not have the basic training, it’s difficult to master how to get into a state of mindfulness. Animation has been shown by many studies to help improve cognition and is often used as a guiding tool. Using animation as the guiding carrier of meditation is more convenient and easier to accept. Therefore, this study adopted the intervention method of animation-guided meditation, aiming to explore: (1) the effect of animation-guided meditation on enhancing creativity; (2) the role of flow and emotion in the influence of mindfulness on creativity. We advertised recruitment through the internal network of a creative industrial park, and the final 95 eligible participants were divided into two groups: animation (n = 48) and audio (n = 47) guided meditation. The animation group was given an animated meditation intervention, and the audio group was given an audio meditation intervention, both interventions were performed 3 times a week and last for 8 weeks. Results: (1) Animation-guided meditation significantly increased participants’ mindfulness and creativity levels; Significantly reduced their cognitive load compared to audio-guided meditation. (2) Mindfulness has a significant direct effect on creativity, and significant indirect effects on creativity; Flow and PA act as the mediating variable. Conclusion: (1) Mindfulness, flow, and PA all helped to improve the subjects’ work creativity. In addition to the direct positive impact of mindfulness on creativity, mindfulness can also have an indirect positive impact on creativity through flow and PA. (2) Compared with audio, animation can significantly reduce cognitive load and help improve users’ cognitive ability, which is more suitable for the guidance materials of mindfulness meditation to enhance the effect of meditation.